Հոռոմոսի վանքը և գրչատունը - Մաթևոսյան, Կարեն (Մատենադարան)
One of the famous and large monasteries of medieval Armenia is Hoṛomos near Ani (now in Turkey). The monastery was founded shortly before Ani became the capital of Armenia, in the 30s-40s of the 10th century, but its further history and rise are associated with Ani. In 961, King Ashot III Bagratuni, having proclaimed Ani as capital, turned the monastery of Hoṛomos into the burial place of the kings. Here the kings of Ani built three churches, the largest of which was St. Yovhannēs (1038). Hoṛomos was still a flourishing monastery in the 13th–14th centuries. In the 15th century, the population of Ani had emigrated and the city was empty, but the monastery of Hoṛomos lasted until the beginning of the 20th century. The churches and other buildings of the monastery are currently in poor condition. In the Middle Ages, a scriptorium operated in the monastery of Hoṛomos, where many manuscripts were copied. Particularly noteworthy are scribes Yovhannēs (12th century) and Ignatios (13th century) who were also skilled miniaturists. Один из известных и крупных монастырей средневековой Армении – Оромос вблизи Ани (ныне на территории Турции). Монастырь был основан незадолго до того, как Ани стал столицей Армении, в 30-40-х годах X века, однако его дальнейшая история и подъем связаны именно с Ани. В 961 г. царь Ашот III Багратуни, провозгласив Ани столицей, превратил монастырь Оромос в место погребения царей. Здесь анийские цари построили три церкви, наибольшей из которых была Св. Ованес (1038). Оромос процветал и в XIII-XIV веках. В XV веке население Ани эмигрировало, и город опустел, но монастырь Оромос просуществовал до начала 20-го века. В настоящее время церкви и другие постройки монастыря находятся в плачевном состоянии. В средние века в монастыре Оромос действовал скрипторий, в котором было создано множество рукописей. Особого внимания заслуживают писцы Ованес (XII в.) и Игнатиос (XIII в.), которые были искусны также и в миниатюре.
Keywords: Հայոց եկեղեցու պատմություն; Աղբյուրագիտություն